SOME GARRISON AND COMMAND REGIMENTAL SERGEANT MAJORS AT THE CASTLE OF GOOD HOPE IN CAPE TOWN - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Whilst the names of the officers who have commanded our commands and regiments have been recorded and are in many cases well known, the same cannot be said for all our garrison and regimental sergeant majors. Unlike unit commanders, regimental sergeant majors do not sign a handing over certificate on appointment, so it is often very difficult to establish who the successive regimental sergeant majors of some of our units where.’ However, by good fortune and some guesswork, which yielded unexpectedly good results it has been possible to fill another gap in our knowledge about some of those who have served at the Castle of Good Hope.